Hubungan Dimensi Kepribadian The Big Five Personality dengan Penyesuaian Diri Mahasiswa Asing di Universitas Udayana - Demira Shaifa; Supriyadi Supriyadi (Jurnal Psikologi Udayana, 2013)
International students are vulnerable to have adjustment issues and faced stressful events when they study abroad (Yusoff & Chelliah, 2006). How they cope with adjustment issues depends on their unique personality (Ward, Leong, & Low, 2004). This quantitative research with correlational approach is aimed to find out the relationship between personality dimensions from The Big Five Personality and adjustment of international students in Udayana University. One hundred and forty five international exchange students across nations who stayed in Bali for maximum of one year and have a course in Udayana University became subject of this research. Personality was measured by The Big Five Inventory (reliability = 0,946) and sojourner adjustment was measured by Sojourner Adjustment Measure that modified from Pedersen’s (2011) version (reliability = 0,785). Data has a normal distribution, those are p = 0,776 for personality and p = 0,199 for adjustment and also has a linear model (p = 0,000). Partial correlation was performed to do the analysis. The result indicates that there are positive and significant relationship between agreeableness (r = 0,285, p < 0,05) and openness to new experience (r = 0,136, p < 0,05) towards adjustment of international students in Udayana University. However, there are no significant relationship found in extraversion, conscientiousness, and neuroticism towards adjustment of international students in Udayana University. Keywords: personality, The Big Five Personality, sojourner adjustment, international students.